The Effect of Immigration on Business Dynamics and Employment - Pia M. Orrenius; Madeline Zavodny; Alexander Abraham (Institute of Labor Economics (IZA), 2020)
Immigration, like any positive labor supply shock, should increase the return to capital and spur business investment. These changes should have a positive impact on business creation and expansion, particularly in areas that receive large immigrant inflows. Despite this clear prediction, there is sparse empirical evidence on the effect of immigration on business dynamics. One reason may be data unavailability since public-access firm-level data are rare. This study examines the impact of immigration on business dynamics and employment by combining U.S. data on immigrant inflows from the Current Population Survey with data on business formation and survival and job creation and destruction from the National Establishment Time Series (NETS) database for the period 1997 to 2013. The results indicate that immigration increases the business growth rate by boosting business survival and raises employment by reducing job destruction. The effects are largely driven by less-educated immigrants.
Keywords: J15; J61; L25; 330; immigration; business dynamics; firm entry; firm exit; job creation; job destruction